2005
DOI: 10.1007/s00428-005-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery changes in patients with primary renal cell carcinoma

Abstract: Arterial fibromuscular dysplasia (FMD) is a non-inflammatory, non-atherosclerotic, occlusive condition of the systemic arteries, most frequently affecting renal arteries. Renal cell carcinoma (RCC) might be associated with arterial hypertension, however, there are no data in the literature regarding the relationship between RCC and associated renal artery changes.We analyzed a consecutive series of 57 (35 male and 22 female) patients aging from 35 to 79 years (mean 58.9 years) who underwent nephrectomy due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…Although the present as well as previous studies [11,20] pointed to a high rate of renal artery lesions in RCC patients, we found no significant differences in renal artery diameter or media layer thickness between renal arteries without changes and those with FMD or atherosclerotic lesions. This finding was not unexpected since our study of the control group as well as other studies [4,12,16,19] showed renal artery changes to be mostly segmental, with only a small part of renal artery being available for sampling and histological examination after radical nephrectomy due to RCC.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Although the present as well as previous studies [11,20] pointed to a high rate of renal artery lesions in RCC patients, we found no significant differences in renal artery diameter or media layer thickness between renal arteries without changes and those with FMD or atherosclerotic lesions. This finding was not unexpected since our study of the control group as well as other studies [4,12,16,19] showed renal artery changes to be mostly segmental, with only a small part of renal artery being available for sampling and histological examination after radical nephrectomy due to RCC.…”
Section: Discussioncontrasting
confidence: 88%
“…The majority of authors suggest that decreased tumor microvessel density leads to chronic hypoxia of the tumor tissue, which then causes coagulative necrosis [10,17]. However, some authors suggest that pathologic changes in renal arteries could also be responsible for tumor necrosis in RCC [11,20]. Different lesions, most frequently atherosclerosis, and less commonly fibromuscular dysplasia (FMD) or some other conditions such as Takayasu arteritis, radiation injury and congenital malformations [15], may affect the main renal artery.…”
Section: Tomic Et Al 3 Introductionmentioning
confidence: 99%
“…In our previous study, renal artery changes were observed in 31 of 57 patients with RCC. 17 Fibromuscular dysplasia was found in 24 patients and atherosclerosis in an additional 7. In this present study, we observed tumor necrosis in 78.6% of RCCs, with a significant correlation between the presence and type of FMD and the extent of the RCC necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, there are few data on the relationship between renal artery changes, including FMD-like changes, and RCC. 17 Onishi et al 18 reported histologic features of hypovascular and avascular RCC; however, the cause of vascular changes was not further analyzed. In our previous study, renal artery changes were observed in 31 of 57 patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological renal artery changes are found in a high percentage of patients with RCC [15,16]. The results of one morphometric study showed that renal arteries in a group of patients with RCC have a thicker tunica media layer than those in the control group (without RCC) [17].…”
Section: Introductionmentioning
confidence: 96%